2019
DOI: 10.35675/befdergi.430390
|View full text |Cite
|
Sign up to set email alerts
|

An Example For Comparative Social Studies Teaching: The Perceptions of Turkish and Russian Secondary School Students Towards “Good Citizenship”

Abstract: ÖzBu araştırmanın amacı, karşılaştırmalı eğitime bir örnek olması için Türk ve Rus ortaokul öğrencilerinin iyi vatandaşlık algılarını ortaya koymaktır. Araştırmada nitel araştırma yönteminden, durum çalışması modeli kullanılmıştır. Araştırmanın çalışma grubundaki Türk ortaokul öğrencilerini Antalya merkezdeki bir ortaokulun 7. ve 8. sınıf öğrencileri (toplam 31 öğrenci) oluşturmuştur. Çalışma grubundaki Rus ortaokul öğrencilerini ise Antalya'da özel bir yabancı okulda öğrenim gören 24 öğrenci oluşturmuştur. Ça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The acquisitions in the Russian textbook are more universal. The results that support this situation are achieved in the studies of Akhan and Cicek (2019) and .…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 65%
See 3 more Smart Citations
“…The acquisitions in the Russian textbook are more universal. The results that support this situation are achieved in the studies of Akhan and Cicek (2019) and .…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 65%
“…In this case, Turkey and it expressed in the work program to be dependent on social information processing in Russia. Also, in Akhan et al's (2019) study, it appears that Russia's social studies curriculum takes place in the form of a universal citizens by raising Turkey. This situation, namely the fact that Russia refrains from emphasizing the local because of its more cosmopolitan public structure can be explained by the understanding of uniting different ethnic origins around the understanding of universality.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, Akhan, Babaev, and Çiç ek (2019) revealed in their studies that Russia's educational goals are based on more universal and humanitarian values compared to the Turkish education system. In Akhan and Çiç ek (2019), it was observed that Turkish students expressed good citizenship in a more nationalist framework than Russian students while Russian students expressed good citizenship more universally. The researchers explained these results with reference to the difference in classroom practices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%